How much blue light should an IOL transmit?. Issue 12 (5th December 2003) - Mainster, M A; Sparrow, J R
Abstract : Older, and even some modern, intraocular lenses (IOLs) transmit potentially hazardous ultraviolet radiation (UVR) to the retina. In addition, IOLs transmit more blue and green light to the retina for scotopic vision than the crystalline lenses they replace, light that is also potentially hazardous. The severity of UVR-blue type phototoxicity increases with decreasing wavelength, unlike the action spectrum of blue-green type retinal phototoxicity and the luminous efficiency of scotopic vision which both peak in the blue-green part of the optical spectrum around 500 nm. Theoretically, UVR+blue absorbing IOLs provide better retinal protection but worse scotopic sensitivity than UVR-only absorbing IOLs, but further study is needed to test this analysis. UVR is potentially hazardous and not useful for vision, so it is prudent to protect the retina from it with chromophores in IOLs. Determining authoritatively how much blue light an optimal IOL should block requires definitive studies to determine (1) the action spectrum of the retinal phototoxicity potentially involved in human retinal ageing, and (2) the amount of shorter wavelength blue light required for older adults to perform essential activities in dimly lit environments.